A genome-wide siRNA screen identifies a druggable host pathway essential for the Ebola virus life cycle - Martin, Scott; Chiramel, Abhilash I.; Schmidt, Marie Luisa; Chen, Yu-Chi; Whitt, Nadia; Watt, Ari; Dunham, Eric C.; Shifflett, Kyle; Traeger, Shelby; Leske, Anne; Buehler, Eugen; Martellaro, Cynthia; et al. (Genome medicine, 2018)
The 2014-2016 Ebola virus (EBOV) outbreak in West Africa highlighted the need for improved therapeutic options against this virus. Approaches targeting host factors/pathways essential for the virus are advantageous because they can potentially target a wide range of viruses, including newly emerging ones and because the development of resistance is less likely than when targeting the virus directly. However, systematic approaches for screening host factors important for EBOV have been hampered by the necessity to work with this virus at biosafety level 4 (BSL4). In order to identify host factors involved in the EBOV life cycle, we performed a genome-wide siRNA screen comprising 64,755 individual siRNAs against 21,566 human genes to assess their activity in EBOV genome replication and transcription. As a screening platform, we used reverse genetics-based life cycle modelling systems that recapitulate these processes without the need for a BSL4 laboratory. Among others, we identified the de novo pyrimidine synthesis pathway as an essential host pathway for EBOV genome replication and transcription, and confirmed this using infectious EBOV under BSL4 conditions. An FDA-approved drug targeting this pathway showed antiviral activity against infectious EBOV, as well as other non-segmented negative-sense RNA viruses. This study provides a minable data set for every human gene regarding its role in EBOV genome replication and transcription, shows that an FDA-approved drug targeting one of the identified pathways is highly efficacious in vitro, and demonstrates the power of life cycle modelling systems for conducting genome-wide host factor screens for BSL4 viruses.